1999
DOI: 10.1002/etc.5620180725
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation profiles of polychlorinated biphenyl congeners and organochlorine pesticides in Ganges river dolphins

Abstract: Isomer‐specific concentrations of polychlorinated biphenyls (PCBs) including non‐, mono‐, and di‐ortho‐substituted congeners, DDT and its metabolites, hexachlorocyclohexane (HCH) isomers, chlordane compounds, and hexachlorobenzene (HCB) were determined in river dolphin blubber and prey fishes collected during 1993 through 1996 from the River Ganges in India. Concentrations of organochlorines were also measured in the milk and liver of dolphins, benthic invertebrates, and sediments. The DDTs and PCBs were the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 38 publications
4
25
0
Order By: Relevance
“…Due to their chemical properties, HCHs are easily volatilized and transported by air and water currents for long distances (Iwata et al, 1993;Wania and Mackay, 1993). Although Canada, Europe, and the U.S. have banned HCHs since the 1970s, several tropical countries still used lindane (pure g-HCH) until the 1990s (Li et al, 2003;Senthilkumar et al, 2001Senthilkumar et al, , 1999, influencing thus the occurrence of g-HCH in Antarctic food webs. Humpback whales feeding in the Antarctic Peninsula region displayed a high percent contribution of lindane (g-HCH) to the SHCH, as a consequence of lindane use in South America close to the Peninsula (Dorneles et al, 2015).…”
Section: Contamination Profile Of Humpback Whales Off La Reunion Islandmentioning
confidence: 99%
“…Due to their chemical properties, HCHs are easily volatilized and transported by air and water currents for long distances (Iwata et al, 1993;Wania and Mackay, 1993). Although Canada, Europe, and the U.S. have banned HCHs since the 1970s, several tropical countries still used lindane (pure g-HCH) until the 1990s (Li et al, 2003;Senthilkumar et al, 2001Senthilkumar et al, , 1999, influencing thus the occurrence of g-HCH in Antarctic food webs. Humpback whales feeding in the Antarctic Peninsula region displayed a high percent contribution of lindane (g-HCH) to the SHCH, as a consequence of lindane use in South America close to the Peninsula (Dorneles et al, 2015).…”
Section: Contamination Profile Of Humpback Whales Off La Reunion Islandmentioning
confidence: 99%
“…Tanabe et al [68] and Takeoka et al [69] evaluated the transport of HCHs from land to sea in a paddy field and adjoining estuarine systems in southern India and found out that major portion of the HCHs used is removed to the air and contribute both to the regional and global pollution. A series of studies from other workers showed the existence of various pesticides in samples of air [70][71][72][73], water [70,[74][75][76][77][78][79][80][81][82][83][84][85], soil and sediments [69][70][86][87][88][89][90][91][92][93][94][95][96][97][98] wildlife including dolphins, sharks and mussels [99][100][101][102][103][104][105][106][107], fish [106,108,109] birds [88,…”
Section: Locationmentioning
confidence: 99%
“…4, most of OCs accumulated in the archived samples of Baikal seals (Phoca sibirica), a representative species living in inland water, were on a declining trend during 1992-2002 Tsydenova et al 2004). This result indicates that the regulation of OC production and usage following the recommendation by World Health Organization (WHO), Food and Agriculture Organization 1988/1992-1994/1996(Senthilkumar et al 1999Tanabe et al 2003). In particular, levels of PCBs, DDTs and HCHs in Ganges River dolphin increased about 2.5 times during the study period.…”
Section: Status Of Contamination and Distributionmentioning
confidence: 73%